Measurement and Analysis of Abrasive Particles Velocities in AWSJ. (2016) - Zeleňák, M.; Foldyna, J.; Linde, M.; Pude, F.; Rentsch, T.; Fernolendt, J.; Poort, H.U.
Abstract: Abrasive water suspension (AWS) is a progressive cutting technology used in many industrial applications. Potential of this technology is very high due to good mobility and flexibility of the cutting process. It is mainly applied in the fields of defusing explosives, repairing and dismantling of nuclear power plants, offshore applications and special industrial structures. Although this technology works very well, further improvement of basic components and optimization of the cutting process is vital. In this experimental work, the applicability of LIF (Laser Inducted Fluorescence) technique combined with PTV (Particle Tracking Velocity) was tested for the identification of velocities of abrasive particles at the output of a cutting nozzle. The combination of various pressure levels with different abrasive mass concentration was tested. The obtained results of abrasive particle velocities are presented in the paper.